Design, development, and fabrication of a 6 DOF humanoid welding robot manipulator - Hajjaj S.S.H.; Khonbreh M. (Asian Research Publishing Network, 2023)
This work reports on the design, development, and fabrication of humanoid welding robot manipulator with 6 D.O.Fs. By mimicking the movement and motion of the human hand, this robotic welder manipulator could mimic or even surpass the performance of the human welder. This work is a component of a bigger project on Human-Robot Interaction (HRI). The objective of this work mainly is to focus on mechanical design of the manipulator. That includes analyzing the human hand, arm and developing a robotic manipulator to mimic some or most of the motions of the human arm, from the shoulder to the wrist. Kinematics analysis of the human arm, joints, and linkage structure were conducted in Creo, AutoCAD. These were used in the fabrication and development of a working prototype. This project was developed in collaboration with another project; namely the humanoid gripper. As such, upon construction of this manipulator, it was attached to the humanoid gripper and allowed to manipulate it and allow it perform its function of gripping objects, pick and place, and perform a human gesture. Results obtained from this work illustrated the good functionality of the design. 2006-2015 Asian Research Publishing Network (ARPN).